STATE OF THE RURAL COMMUNITY ON THE LADDER OF PUBLIC PARTICIPATION: CASE STUDY WASTE MANAGEMENT PROGRAM IN MOJOSARI VILLAGE, BOJONEGORO REGENCY - Hidayah, Nurul; Meidiana, Christia; Firdausiyah, Nailah; Ghosh, Ratan Kumar; Amalia, Rizky (Journal of Environmental Engineering and Sustainable Technology, 2024)
The success of waste management must be connected to the community's participation. The community's involvement in waste management still needs to be significantly apparent. Community participation in rural waste management programs was investigated in this study since the waste reduction activities still involve open burning and burying of waste in the yard, which is harmful to the environment. A research model was designed, and a questionnaire was distributed among 112 households (HHs) to analyze their participation in rural waste management programs. A semi-structured questionnaire survey, focus group discussions, and key informant interviews were adopted to acquire qualitative information. The analytical framework includes mass balance analysis (MBA) and Arnstein's participation (APL) ladder. MBA was applied to measure each HH's current waste reduction rate, while (APL) was used to evaluate the community participation level in this program. The findings revealed that the average waste reduction is 0,48 kg/HH/day, contributing to a total waste reduction of 17.94 kg/day in the village (24.39% of total waste generation). Measurement using APL unfolds that the extant community participation in Mojosari Village, Bojonegoro Regency, corresponds to a non-participation continuum where villagers are simply misled by pseudo and tokenistic participation, leading to unequal benefit-sharing. Based on these findings, the researchers challenge that communities' engagement in rural waste management mainly relies on community cadres concerning environmental subjects as well as communities' economic backgrounds. It is concluded that where economically weak communities and manipulative figures exist, ensuring a higher community participation level is more challenging.